2016
DOI: 10.1002/art.39542
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Nonradiographic Axial Spondyloarthritis to Ankylosing Spondylitis: A Population‐Based Cohort Study

Abstract: Objective The long-term outcome of patients with non-radiographic axial spondyloarthritis (nr-axSpA) is unclear, particularly whether few or most progress to ankylosing spondylitis (AS). Our objective was to examine the progression to AS in a population-based inception cohort of patients with nr-axSpA. Methods The Rochester Epidemiology Project (REP) is a longstanding population-based study of health in the residents of Olmsted County, Minnesota. We searched the REP from 1985 to 2010 using diagnostic and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 21 publications
1
49
2
1
Order By: Relevance
“…The findings of the present study (a low rate of progression after a 2‐year follow‐up period) do not confirm the usual 10% rate (i.e., 10% of patients with nonradiographic structural damage will switch to radiographic structural damage after 2 years of follow‐up) that is frequently mentioned in reviews . The low rate of progression observed in the present study has recently been confirmed in a population‐based cohort study, with 6.4%, 17.3%, and 26.4% of patients switching from nonradiographic to radiographic disease after 5, 10, and 15 years of follow‐up, respectively .…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the present study (a low rate of progression after a 2‐year follow‐up period) do not confirm the usual 10% rate (i.e., 10% of patients with nonradiographic structural damage will switch to radiographic structural damage after 2 years of follow‐up) that is frequently mentioned in reviews . The low rate of progression observed in the present study has recently been confirmed in a population‐based cohort study, with 6.4%, 17.3%, and 26.4% of patients switching from nonradiographic to radiographic disease after 5, 10, and 15 years of follow‐up, respectively .…”
Section: Discussioncontrasting
confidence: 99%
“…Progression to ankylosing spondylitis occurs in only a minority of patients who have had nonradiographic axial spondyloarthritis for a decade or more. 12 It is unclear whether nonradiographic axial spondyloarthritis and ankylosing spondylitis reflect a single entity that varies along a continuum of duration and severity or whether nonradiographic axial spondyloarthritis includes one or more pathogenetically distinct subsets of disease that either have not been previously recognized or have been given other diagnoses, including undifferentiated spondyloarthritis. [13][14][15] Among patients with nonradiographic axial spondyloarthritis, there is a significantly higher proportion of female patients, a shorter median duration of disease, and lower levels of inflammatory markers than among those with ankylosing spondylitis.…”
mentioning
confidence: 99%
“…It is also important to acknowledge that the current “gold standard” for identifying sacroiliitis, is neither 100% sensitive nor specific for these articular structures. Recently, the use of MRI as criterion for classification of nrAxSpA has been questioned . A population‐based cohort study showed only a minority (26%) of patients presenting with MRI inflammation evolving to AS (the radiographic subset of the disease) with an average follow‐up of 10 years .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of MRI as criterion for classification of nrAxSpA has been questioned . A population‐based cohort study showed only a minority (26%) of patients presenting with MRI inflammation evolving to AS (the radiographic subset of the disease) with an average follow‐up of 10 years . Furthermore, MRI inflammatory changes are also seen in individuals who have had recent mechanical stress, such as runners as well as women in the post‐partum period .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation